2010
DOI: 10.1021/la904616s
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Self-Assembly of Monodisperse Niosomes by Microfluidic Hydrodynamic Focusing

Abstract: Niosomes are synthetic membrane vesicles formed by self-assembly of nonionic surfactant, often in a mixture with cholesterol and dicetyl phosphate. Because of their inner aqueous core and bilayer membrane shell, niosomes are commonly used as carriers of treatment agents for pharmaceutical and cosmetic applications or contrast agents for clinical imaging applications. In those applications, niosomes are considered as a more economical and stable alternative to their biological counterpart (i.e., liposomes). How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 38 publications
5
75
0
Order By: Relevance
“…Earlier studies have demonstrated the ability of vesicles synthesized by the microfluidics approach to encapsulate hydrophilic molecules including DNA fragments [25,29,54]. It has also been shown previously [25,30,43] and in this study that hydrophobic dye molecules can be incorporated in the vesicle lipid bilayer. All of these results show capability of the MHF approach to synthesize unilamellar lipid vesicles loaded with a versatile set of hydrophilic and hydrophobic molecules that can be used in simplified models of cellular compartments.…”
Section: Figuresupporting
confidence: 77%
See 1 more Smart Citation
“…Earlier studies have demonstrated the ability of vesicles synthesized by the microfluidics approach to encapsulate hydrophilic molecules including DNA fragments [25,29,54]. It has also been shown previously [25,30,43] and in this study that hydrophobic dye molecules can be incorporated in the vesicle lipid bilayer. All of these results show capability of the MHF approach to synthesize unilamellar lipid vesicles loaded with a versatile set of hydrophilic and hydrophobic molecules that can be used in simplified models of cellular compartments.…”
Section: Figuresupporting
confidence: 77%
“…As DiI is a lipid intercalating dye whose fluorescence quantum efficiency increases substantially when embedded in a lipid bilayer compared with its aqueous solution [43], a strong fluorescence should be observed under the microscope if liposomes are formed. Strong fluorescence is indeed seen here as shown in Figure 3, offering further proof that POPC liposomes have been synthesized in the microfluidic process.…”
Section: Figurementioning
confidence: 99%
“…The two phases are introduced in a coaxial manner, with the central aqueous stream being sheathed by the outer ethanol stream and hydrodynamically focused ( i. e ., hydrodynamic flow focusing). The flow in the fluidic channel follows a laminar‐flow pattern even at relatively high flow rates, while the mixing between aqueous NaCl and ethanol is dominated by molecular diffusion . Upon contact between the two phases, NaCl nanocrystals are precipitated out at the interface and a concentration gradient of NaCl in the aqueous phase will be created along the flow direction.…”
Section: Introductionmentioning
confidence: 99%
“…The flow in the fluidic channel follows a laminar-flow pattern even at relatively high flow rates, while the mixing between aqueous NaCl and ethanol is dominated by molecular diffusion. [18,19] Upon contact between the two phases, NaCl nanocrystals are precipitated out at the interface and a concentration gradient of NaCl in the aqueous phase will be created along the flow direction. We can regulate the concentration gradient by adjusting the hydrodynamic parameters to control the nucleation and growth of NaCl nanocrystals and thus their size and size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Span20 mostly consists of a fully saturated short alkyl chain (lauryl - C12). The single carbon bonds in Span20 allow the alkyl chain to pack tightly, resulting in the smallest and stable niosomes, oppose to the niosomes consisting of longer chain surfactants, Spans40–80 (Lo et al, 2010, Hao et al, 2002, Israelachvili et al, 1980). Vesicles prepared by Span-series surfactants have been reported to be viable drug carriers for different diseases and different routes of administration(Ghanbarzadeh et al, 2015, Balakrishnan et al, 2009, Sahoo et al, 2014, Liu et al, 2017, Ammar et al, 2011, Guinedi et al, 2005, Hunter et al, 1988, Jadon et al, 2009, Pardakhty et al, 2007).…”
Section: Introductionmentioning
confidence: 99%